2020
DOI: 10.4103/jpbs.jpbs_340_19
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals poisoning: Reported by the National Poison Centre in Malaysia between 2010 and 2015

Abstract: A BSTRACT Background and Purpose: The wide availability of medications has led to an increased exposure of humans to the possibility of poisoning. An unavoidable effect due to the availability of these medications has also led to a rising increment in the number of poisoning cases. All drugs, especially when administered in large doses or overextended periods, can initiate a toxic condition. Therefore, the objective of this study was to examine nationwide, the patterns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Studies were included if they fulfilled the following criteria: (1) the study reported on poisoning due to pharmaceuticals; (2) the published date was between 1 January 2011-31 December 2020; (3) full texts and abstracts were available in English; (4) the country where the study was conducted was stated; and (5) the article stated both the reason(s) (e.g., accidental or intentional) and outcome(s) (e.g., length of hospital stay, morbidity or mortality) of the poisoning. Studies were excluded from this review if: (1) they reported on poisoning due to toxins other than medicines (e.g., household products, pesticides etc.)…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were included if they fulfilled the following criteria: (1) the study reported on poisoning due to pharmaceuticals; (2) the published date was between 1 January 2011-31 December 2020; (3) full texts and abstracts were available in English; (4) the country where the study was conducted was stated; and (5) the article stated both the reason(s) (e.g., accidental or intentional) and outcome(s) (e.g., length of hospital stay, morbidity or mortality) of the poisoning. Studies were excluded from this review if: (1) they reported on poisoning due to toxins other than medicines (e.g., household products, pesticides etc.)…”
Section: Study Selectionmentioning
confidence: 99%
“…Toxic exposure to medicines remains a significant, under-recognised global public health concern. The World Drug Report estimates that pharmaceutical poisoning causes 190,000 fatalities annually [1]; with non-fatal poisoning 20-30 times more prevalent and often causing long-term morbidities [2]. The most prevalent long-term conditions are respiratory, renal or hepatic failure, cognitive impairment, and hypoxic brain injury, depending on the drug(s) involved [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxic exposure to medicines remains a significant, under-recognised global public health concern. The World Drug Report estimates that 190,000 deaths yearly are linked to pharmaceutical poisoning [1]; with reports showing that non-fatal poisoning is 20-30 times more likely than fatal poisoning, often leaving patients with long-lasting morbidities [2]. These long-term conditions depend very much on the drug(s) the patient has been exposed to, the most common being respiratory, renal, or hepatic failure, cognitive impairment, and hypoxic brain injury [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these patients are prescribed drugs to help manage their condition, highlighting the magnitude of the population's vulnerability and exposure to medicines with potential toxicity. In Asia specifically, over 60% of drug poisoning suicides are from people diagnosed with a psychiatric condition highlighting the correlation between poor mental health and pharmaceutical poisoning [1,15,16]. Furthermore, the act of overdosing with prescribed and over-the-counter medicines is estimated to be responsible for 79% of presentations to emergency departments due to self-harm in the UK [3,16,17].…”
Section: Introductionmentioning
confidence: 99%